Short-term functional outcomes of robotic-assisted TKA are better with functional alignment compared to adjusted mechanical alignment - Jeffrey, Michaud; Marchand, Philippe; Kouyoumdjian, Pascal; Coulomb, Remy (SICOT-J, 2024)
Introduction : Ligament balancing is essential to the functional outcome of total knee arthroplasty (TKA). The optimal method of alignment remains a controversial issue. The primary objective was to compare the clinical outcomes of TKA between functional and adjusted mechanical alignment techniques. The secondary objectives were to compare bone resection, robotic alignment, and radiological assessment. Materials and methods : This was a retrospective case-control series comparing TKA performed with functional alignment (FA) and adjusted mechanical alignment (aMA). Sixty-four FA subjects were matched with 64 aMA controls. These two groups were matched for age, gender, body mass index (BMI), surgeon, and type of frontal deformity. Both surgical procedures were performed using the MAKO ® haptic robotic system. Functional scores (Forgotten Joint Score (FJS), Knee Society Score (KSS), and Oxford Knee Score (OKS)) were measured at the final postoperative follow-up. A radiographic evaluation was performed at the same time. Results : Mean FJS were respectively 63.4 ± 25.1 [0–100] and 51.2 ± 31.8 [0–100] in FA versus aMA group ( p = 0.034). Mean OKS were respectively 40.8 ± 6.3 [21–48] and 34.9 ± 11.8 [3–48] in FA versus aMA group ( p = 0.027). Mean KSS were respectively 184.9 ± 17.0 [126–200] and 175.6 ± 23.1 [102–200] in FA versus aMA group ( p = 0.02). The main residual symptom was “none” for 73.0% versus 57.8%, “instability” for 6.4% versus 21.9%, “Pain” for 19.1% versus 12.5%, and “effusion” for 1.6% and 7.8% respectively for FA and aMA group ( p = 0.016). There were 4 complications in the FA group versus 5 in the aMA group ( p > 0.999). Mean postoperative hip-knee-ankle (HKA) robotic assessment were respectively 177.3° ± 2.0 [172–180] and 178.2° ± 2.0 [173–180] for FA and aMA group ( p = 0.018). The median difference between HKA robotic and HKA radiological was −3.0° (IQR = 3.0; p < 0.001). Conclusion : With greater residual deformity and without release, functional alignment showed a statistically significantly better short-term clinical outcome than adjusted mechanical alignment. This difference may not be clinically significant.